Preoperative Non-ambulatory Status Predicts Poor Outcome after Below Knee Bypass Surgery - Yamamoto, Kota (Japanese College of Angiology, The Japanese Society for Vascular Surgery, Japanese Society of Phlebology, 2011)
Objective: To identify the outcome of below knee bypass that focuses on the functional status and to investigate whether preoperative functional status can predict these outcomes. Materials and Methods: One hundred and fifty one limbs in one hundred and thirty two patients that underwent below knee bypass between 2004 and 2008 were retrospectively reviewed. The patients were grouped as “ambulatory,” “non-ambulatory transfer” and “non-ambulatory bedridden,” according to their functional status. Clinical success was defined as the achievement of all of following end points; graft patency to wound healing, limb salvage for 1 year or until death, maintenance of ambulatory status for 1 year, and survival for 6 months. The effect of preoperative ambulatory status was analyzed. Results: The overall primary and secondary graft patency, limb salvage and survival at 1 year were 76.3%, 81.8%, 89.1% and 84.1%, respectively. The overall success rate was 62.0%. Clinical success rates for the ambulatory and non-ambulatory groups were 75.6% and 34.9% (P = 0.0009, OR: 4.4; 95% CI: 1.8–10.6). Conclusions: Bypass surgery is justified for maintaining the independent status of ambulatory patients. On the other hand, the high likelihood of poor outcomes for non-ambulatory patients must be considered before performing bypass surgery.